Lower Posttraumatic α-Synuclein Level Associated With Altered Default Mode Network Connectivity Following Acute Mild Traumatic Brain Injury - Ye, Limei; Zhang, Danbin; Shao, Meihua; Zhao, Pinghui; Yin, Bo; Zhuang, Jinfei; Wang, Feifei; Yan, Zhihan; Bai, Guanghui (Frontiers in Neural Circuits, 2019)
This study aimed to investigate the changes of α-synuclein in serum and its relationship with default mode network connectivity after acute mild traumatic brain injury (mild TBI). Fifty-two patients with mild TBI at acute phase and forty-seven matched healthy controls were enrolled in the study. All participants received resting-state functional magnetic resonance imaging and neuropsychological assessments. Relations between the levels of α-synuclein in serum and clinical assessments were obtained using multivariate linear regression. Results showed that the patients with lower α-synuclein presented more complaints on post-concussion symptoms and depression. Moreover, patients with high levels of α-synuclein exhibited significantly decreased functional connectivity in the left precuneus and increased functional connectivity in both the left anterior cingulate cortex and ventro-medial prefrontal cortex compared with patients with low levels of α-synuclein. These findings supported that α-synuclein may modulate the functional connectivity within the default mode network and suggest the feasibility of using α-synuclein as objective biomarker for diagnosis and prognosis of mild TBI.